Enhancing Healthcare Predictions with Deep Learning Models - Baji, Adam (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
This study leverages Convolutional Neural Networks (CNNs) and Recurrent Neural Networks (RNNs) to enhance diagnostics and predictions in healthcare. By training on extensive healthcare datasets, this project aims to improve early disease detection and health risk assessments. Evaluation emphasizes accuracy, reliability, and ethical considerations, including bias mitigation. This research promises to bridge AI advancements and clinical applications, offering significant improvements in diagnostic capabilities and healthcare accessibility.